Interpretation of Fascism and Ideological Struggle - Lempertas, Izraelis (Problemos, 1984)
The interpretation of Fascism by the bourgeois historiography in the context of ideological struggle is considered in the article. Basing on the conceptions of totalitarian ism, plurality of fascism, psychoanalytical conceptions, the views of E. Nolte and Lithuanian bourgeois emigrants, it is shown how the class interest and striving for relieving monopolies of responsibility for the crimes of Fascism lead bourgeois authors away from the fundamental problems of studying Fascism, “correct” their conclusions. A research into the class roots of Fascism and its class nature is considered to be the major task in the Marxist methodology of studying Fascism. Abandoning this position gives rise not only to ideological confusion but also to theoretical mistakes. In the article the above is proved basing on some conclusions drawn by P. Lossovsky.